Partnerships in Africa in the New Era of Internationalization - Teferra, Damtew (International Higher Education, 2011)
One of the popular approaches to revitalize higher education in Africa and the buzzword of the sector currently is partnership. With the declaration of higher education as vital development tool, multilateral and bilateral regimes, foundations, and other development partners now favor the support of the sector, among other avenues, through partnership schemes. However, prevalence of competing donor-driven agendas, lack of sustainability, unpredictability of donor resources, poor harmonization, and weak coordination and management still hamper these schemes.